Real Estate Development, Highest and Best Use and Real Options - Marina Bravi (Aestimum, 2013)
The primary aim of this work is to connect the Real Options Theory (ROT) with the real estate investment framework. A great deal of theoretical work exist today; it begun with Merton (1973) and Black & Sholes (1973) and provided new insights into capital budgeting decision-making and new models, used today by corporate managers and practitioners too. Unfortunately, the ROT is not widely used by appraisers respect to the traditional DCF model, even though the developers behaviour gives evidence to the model. It is important to remember that the real estate investments are characterized by irreversible decision and by various sources of risk and uncertainty about future returns, especially when the development process is very long. The flexibility in the real estate investment is related to the alternative uses embedded in the land – traditionally interpreted through the Highest and Best Use approach – and to the characteristics of the building. In fact, the value of vacant land should reflect not only the value based on best immediate use, but also its option value, if the development is delayed and the land is converted into best alternative use in the future. This is also true for the redeveloped urban lands. In brief, this work shows the limits of the traditional analysis (Discounted Cash Flow Model) to capture flexibility in the real estate investment and presents an application – an industrial urban area – implemented by the real option approach within a backward risk-neutral valuation process.